Opportunities for the success of digital Islamic banks in Jordan - Tanash, Hamza Ahmad; Alahmad, Shadi Khalifeh; Tanash, Kholood Ahmed; Badarin, Abdalla Mohammad Al (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to explore the prospects for the success of digital Islamic banks in Jordan by examining the factors that influence customers' attitudes toward adopting digital banking services. A quantitative research approach was employed, utilizing a questionnaire grounded in the Technology Acceptance Model (TAM), which is derived from the Theory of Reasoned Action (TRA). The study surveyed a sample of 556 respondents, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Model validity was confirmed through the Chi-square and SRMR tests. The findings reveal that ease of use, cost, and facilitating conditions significantly influence the perceived usefulness of digital banking. Furthermore, perceived usefulness, security, and awareness were found to impact users’ trust in digital banks. While awareness and social influence showed no direct effect on digital banking adoption, trust emerged as a central mediating factor. Additionally, both perceived usefulness and security indirectly affect adoption through trust, whereas awareness does not exert an indirect influence. The study concludes that there are substantial opportunities for the success of digital Islamic banking in Jordan. It recommends that Islamic banks expand the implementation of digital banking services to reduce operational costs, enhance public awareness, and build trust, factors that are critical to securing long-term success in the digital financial landscape.